Development of a System Evaluation Model Based on CobiT 5.0 and Fuzzy Logic to Improve Coretax Performance - Pracita, Sriayu; Nichen, Nichen; Sahlan, Fahmi (Amkop Management Accounting Review (AMAR), 2025)
This study develops an innovative hybrid evaluation model that integrates COBIT 5.0 and Fuzzy Logic to analyze CoreTax performance. Using a mixed-methods approach, data were collected from 10 respondents through surveys, interviews, and observations, with triangulation to validate the results. The results show a system performance score of 68.5 with a disparity between technical aspects (75.2) and user satisfaction (62.3). The original contribution lies in the development of an Extended Technology Acceptance Model for the mandatory system and a Fuzzy-COBIT integration algorithm that overcomes the limitations of conventional evaluation methods. This model provides a basis for continuous improvement of the CoreTax system.